2020
DOI: 10.1111/jhn.12812
|View full text |Cite
|
Sign up to set email alerts
|

Habitual dietary fibre and prebiotic intake is inadequate in patients with inflammatory bowel disease: findings from a multicentre cross‐sectional study

Abstract: Background: Recommendations for dietary fibre intake in patients with inflammatory bowel disease are highly variable. Despite the potential benefits of prebiotic fibres on the gut microbiome, many patients with inflammatory bowel disease follow a low fibre diet. The present study comprehensively evaluated intakes of total and prebiotic fibres in patients with inflammatory bowel disease, aiming to determine the adequacy of fibre intake and factors that may influence intake. Methods: Outpatients with a formal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
2
12
1
Order By: Relevance
“…Median participant fibre intake in this study was higher than the reported Australian average of 20.7 g [ 7 ] and other studies of individuals with IBDs [ 8 , 16 , 28 ]. The average intake of vegetables, grain, and meat/meat alternatives were also higher in our study population than the reported Australian average [ 29 ] and a Dutch study of individuals with IBDs [ 28 ].…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Median participant fibre intake in this study was higher than the reported Australian average of 20.7 g [ 7 ] and other studies of individuals with IBDs [ 8 , 16 , 28 ]. The average intake of vegetables, grain, and meat/meat alternatives were also higher in our study population than the reported Australian average [ 29 ] and a Dutch study of individuals with IBDs [ 28 ].…”
Section: Discussioncontrasting
confidence: 82%
“…The 2011–2012 Australian National Nutrition and Physical Activity Survey (NNPAS) found that over 70% of adults do not reach the recommended fibre intakes [ 7 ]. Furthermore, individuals with gastrointestinal conditions, especially IBDs and IBS, have been frequently reported to have poorer nutrient intakes, and are unlikely to meet the recommended guidelines for dietary fibre [ 8 ]. These actions are largely shaped by dietary beliefs and behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…The diet is rich in vegetables, fruits and whole grains and therefore also antioxidants, folate, and flavonoids which are considered anti-inflammatory. While the high dietary fibre content supports gut health and the growth of microbial species, potentially regulating the inhibition or production of pro-inflammatory chemokines and cytokines ( Davis et al., 2020 ) and omega-3 PUFAs found in the diet, have been shown to regulate the immune response by inhibiting the activation of pro-inflammatory pathways and reducing cytokine expression ( Giacobbe et al., 2020 ; Giacobbe and Mind, 2021 ). High-dose eicosapentaenoic acid has been shown to improve cognitive symptoms in Attention deficit hyperactivity disorder (ADHD) youth with low baseline levels ( Chang et al., 2018 , 2019 ), while research in animal models has demonstrated inflammation-induced reductions in neurogenesis can be prevented through omega-3 PUFAs intake ( Borsini et al., 2017 ).…”
Section: Dietary Intake and Inflammationmentioning
confidence: 99%
“…The anti-inflammatory effect of vegetable assumption could be explained considering their content in polyphenol compounds with antioxidant effect, folate, and flavonoids [ 35 ], and through their restoration of water loss and electrolyte balance function [ 36 ]. Moreover, the high dietary fiber content supports gut health and the growth of microbial species which potentially modulate the production of pro-inflammatory chemokines and cytokines [ 37 ].…”
Section: Introductionmentioning
confidence: 99%